Emisi Karbon Dioksida Tanah di Bawah Penggunaan Lahan Hutan dan Pertanian di Daerah Aliran Sungai Tanralili: Soil Carbon Dioxide Emissions under Forest and Agricultural Land Uses in the Tanralili Watershed - Marselianti; Rismaneswati; Hazairin Zubair (Jurnal Ecosolum, 2026)
The conversion of forests into agricultural land has the potential to increase soil CO₂ emissions due to changes in soil properties, microbial activity, and land management practices. This study aimed to analyze CO₂ emissions under different land uses in the Tanralili Watershed and their relationship with microbial respiration activity and environmental factors. Soil CO₂ emissions were measured using the chamber method across eight land-use types during three observation periods. Heterotrophic respiration was analyzed through soil incubation, while the relationships between CO₂ emissions and soil temperature, soil moisture, air temperature, and air humidity were analyzed using Pearson correlation analysis. The results showed that the highest CO₂ emissions were found in intensive agricultural land, namely PJ1 at 28.92 t ha⁻¹ yr⁻¹ and PH at 25.01 t ha⁻¹ yr⁻¹, while the lowest emissions were found in the mixed garden (PK) at 16.15 t ha⁻¹ yr⁻¹, and forest land (HP, HS, and HPK) ranged from 9.94–12.2 ton ha⁻¹ yr⁻¹. The emission pattern followed the plant growth stages, with high emissions during the vegetative stage after fertilization, decreasing during the generative stage, and increasing again during the maturation stage. Heterotrophic respiration showed a decreasing trend with increasing soil depth, in line with the decline in soil organic carbon content. CO₂ emissions were positively correlated with soil temperature and air temperature and negatively correlated with air humidity, whereas soil moisture showed no significant relationship with CO₂ emissions. The results indicate that land management, microbial activity, and environmental conditions play important roles in controlling soil CO₂ emissions. Land management should therefore be directed toward low-emission agricultural practices through efficient fertilizer use, increasing soil organic matter, and implementing agroforestry systems to reduce carbon emissions and enhance carbon sequestration.